A parallel hybrid ant-tabu algorithm for integrated emergency vehicle dispatching and covering problem. (10th November 2010) - Ibri, Sarah; Drias, Habiba; Nourelfath, Mustapha
In this paper we propose, implement and analyse a parallel solution to solve an integrated dispatching and covering problem for emergency vehicle fleet management system. The basic sequential algorithm is a coupled ant colony system (ACS) with tabu search heuristic. To speed up this algorithm, we develop a master slave ACS parallel version based on the parallel neighbourhood evaluation approach for the tabu procedure. In experiments we compare synchronisation strategies between the parallel processes and show the impact of inter processes communication frequency and the information exchanged on the efficiency of the algorithm.